An ancestral HIV-2/simian immunodeficiency virus peptide with potent HIV-1 and HIV-2 fusion inhibitor activity - Borrego, Pedro; Calado, Rita; Marcelino, José M.; Pereira, Patrícia; Quintas, Alexandre; Barroso, Helena; Taveira, Nuno (Wolters Kluwer / LWW, 2013)
"Objectives: To produce new fusion inhibitor peptides for HIV-1 and HIV-2 based on ancestral envelope sequences. Methods: HIV-2/simian immunodeficiency virus (SIV) ancestral transmembrane protein sequences were reconstructed and ancestral peptides were derived from the helical region 2 (HR2). The activity of one ancestral peptide (named P3) was examined against a panel of HIV-1 and HIV-2 primary isolates in TZM-bl cells and peripheral blood mononuclear cells and compared to T-20. Peptide secondary structure was analyzed by circular dichroism. Resistant viruses were selected and resistance mutations were identified by sequencing the env gene. Results: P3 has 34 residues and overlaps the N-terminal pocket-binding region and heptad repeat core of HR2. In contrast to T-20, P3 forms a typical a-helical structure in solution, binds strongly to the transmembrane protein, and potently inhibits both HIV-2 (mean IC50, 63.8 nmol/l) and HIV-1 (11 nmol/l) infection, including T-20-resistant isolates. The N43K mutation in the HR1 region of HIV-1 leads to 120-fold resistance to P3 indicating that the HR1 region in transmembrane glycoprotein is the target of P3. No HIV-2-resistant mutations could be selected by P3 suggesting that the genetic barrier to resistance is higher in HIV-2 than in HIV-1. HIV-1-infected patients presented significantly lower P3-specific antibody reactivity compared to T-20. Conclusion: P3 is an HIV-2/SIV ancestral peptide with low antigenicity, high stability, and potent activity against both HIV-1, including variants resistant to T-20, and HIV-2. Similar evolutionary biology strategies should be explored to enhance the production of antiviral peptide drugs, microbicides, and vaccines."
Keywords: Ancestral P3 peptide; Inhibition of HIV-1 and HIV-2 cell fusion and entry; P3 antigenic reactivity; P3 mechanism of action; Resistance to P3